Dimensional Synthesis of Motion Generation of a Spherical Four-bar Mechanism Without Prescribed Input Angles - Liu Wenrui; Si Haotian; Sun Jianwei (Jixie chuandong)
By processing the rigid-body poses by the spherical four-bar rigid-body guidance mechanism in the standard installation position, it is found that the pose feature curves, which are generated by taking the processing to the output curves of the mechanism, lie on circles. The formation mechanism of pose feature curves is analyzed, and the internal relationship between the center angle of the adjacent feature points on the pose feature circles and the coupler angle of the spherical four-bar mechanism is revealed. An input angles determination method is proposed for the spherical four-bar rigid body guidance mechanism in the standard installation position. Then, the method is extended to the spherical four-bar rigid-body guidance mechanism in a general installation position. By optimizing the installation angle parameters of the two-dimensional mechanism and the relative input angle of the two-dimensional mechanism to realize the input angles supplement of the spherical four-bar rigid-body guidance mechanism at the general installation position. Use numerical atlas method to solve the motion generation of the spherical four-bar mechanism without prescribed input angles. Finally, the feasibility and effectiveness of the proposed method are demonstrated by examples.